The Toyota way 14 management principles from the world's greatest manufacturer - Liker, Jeffrey K. (Burlington, NC : McGraw-Hill Audio, 2004)
The Toyota Way explains Toyota's unique approach to lean management -- the 14 principles that drive Toyota's quality and efficiency-based culture
Title from container
Narrated by Grover Gardner
Keywords: Toyota Jidosha Kogyo Kabushiki Kaisha; Production management -- Case studies; Industrial productivity; Corporate culture -- History; Industrial management